Localizing Epileptic Focus with Interictal Scalp EEG in Patients with Focal Cortical Dysplasia - MİDİ, İPEK (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: To assess the localizing value of interictal scalp EEG in epileptic focal cortical dysplasia (FCD) patients. Methods: A retrospective observational study of EEG records of epileptic patients seen at the Marmara University Hospital was performed. EEG and MRI findings were evaluated to detect a possible correlation. Results: EEG findings were consistent with MRI findings in 6 patients (37.5%). Conclusion: EEG findings were irrelevant in 62.5% (n:10) of patients. Additional imaging techniques such as ictal SPECT, MEG etc. will clearly augment the success of lesion localisation in FCD patients.
Keywords: EEG; interictal; focal cortical dysplasia; OUTCOMES; CHILDREN